A generic electronic payment model supporting multiple merchant transactions - Huang, YL; Shieh, SP; Ho, FS (My University, 2000)
This paper presents a generic electronic payment model which is intended for a multi-merchant transaction, in which more than one merchant (the retailer, multiple resellers and content providers) are involved in the distribution of electronic contents. With our payment model, every involved merchant will be notified to verify the license information of a content on the settlement day before the customer actually pays for his purchase. Thus, piracy can be discouraged, intellectual property rights of electronic contents can be protected. Each of the involved merchants can obtain his own deserved share of the customer's payment in accordance with their union agreement on this content. As examples to demonstrate the applications of our generic payment model, two well-known payment systems are enhanced herein, based on our payment model.
Keywords: payment model; electronic commerce; network security; copyright protection; electronic content distribution